Pb-210-derived chronology in sediment cores evidencing the anthropogenic occupation history at Corumbata River basin, Brazil - Bonotto, Daniel Marcos [UNESP]; de Lima, JLN (Springer, 2006)
Activity profiles of excess Pb-210 combined with chemical data determined in two sediment cores from Corumbatai River basin, São Paulo State, Brazil, provided new insights into the reconstruction of historical inputs of anthropogenic constituents, contributing to improving management strategies of the hydrological resources in the basin since most of the municipalities extensively utilize the waters of Corumbatai River and tributaries for drinking purposes, among other uses. Excellent significant relationships between loss on ignition (LOI) and organic matter were found for sediments of both analyzed profiles. Silica was found to be inversely related to organic matter at both analyzed profiles: its decrease accompanied an increase in the specific surface of the sediments. This relationship was confirmed by a great number of inverse significant correlations among silica and oxides Na2O, K2O, CaO, MgO, Al2O3, P2O5, Fe2O3, MnO, and TiO2. It was possible to identify the role of organic matter on adsorption of several oxides/elements in the core sediments profiles. Apparent sediment mass accumulation rates corresponding to 224 and 802 mg cm(-2) year(-1) were obtained, and are compatible with field evidence, indicating a higher value associated with sand mining activities interfering with the natural/normal sedimentation process, due to modifications of the channel drainage.
Keywords: lead-210; sediment cores; chemical elements; Corumbata River basin; Brazil